Continuous Auditory Feedback of Eye Movements: An Exploratory Study toward Improving Oculomotor Control - Boyer, Eric O.; Portron, Arthur; Bevilacqua, Frederic; Lorenceau, Jean (Frontiers in Neuroscience, 2017)
As eye movements are mostly automatic and overtly generated to attain visual goals, individuals have a poor metacognitive knowledge of their own eye movements. We present an exploratory study on the effects of real-time continuous auditory feedback generated by eye movements. We considered both a tracking task and a production task where smooth pursuit eye movements can be endogenously generated. In particular, we used a visual paradigm which enables to generate and control smooth pursuit eye movements (SPEM) in the absence of a moving visual target. We investigated whether real-time auditory feedback of eye movement dynamics might improve learning in both tasks, through a training protocol over eight days. The results indicate that real-time sonification of eye movements can actually modify the oculomotor behavior, and reinforce intrinsic oculomotor perception. Nevertheless, large inter-individual differences were observed preventing us from reaching a strong conclusion on sensorimotor learning improvements.